Conversation analysis of the dialogue in "Love, Simon" film - Pradhitya, Muhammad Putra; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research focuses on the use of pauses and overlaps in the dialogue between characters in the film Love, Simon (2018). It uses Hutchby and Wooffitt’s theory of Conversation Analysis as the main framework. The goal is to explore how pauses and overlaps are used in the dialogue of Love, Simon (2018) film. The data consist of film dialogues containing pauses and overlaps, which were examined using qualitative method. The findings show that pauses often happen when characters feel emotionally vulnerable or try to be polite. Overlaps usually appear in emotional situations like conflict, interruption, or quick reactions. These features are not just technical parts of speech, they also show relationship dynamics and emotional depth. This research shows that small details in talk can carry deep meaning, especially in how people manage emotions, relationships, and identity through communication.